Front Line Surgery : A Practical Approach - Martin,, Matthew J.; Beekley,, Alec C.; Eckert, Matthew J. (Springer International Publishing : Imprint: Springer, 2017)
The second edition of Front Line Surgery expands upon the success of the first edition, providing updated discussion of practical management of commonly encountered combat injuries.This edition reflects the cutting edge of combat casualty care, refined principles of surgical management of specific injury patterns, and incorporation of the spectrum of recent research advancements in trauma care. Each chapter continues to follow the same organization as the first edition. The "BLUF", or bottom line up front, headlines each topic, providing the critical pearls for the reader, followed by a focused and straight forward discussion of management, pitfalls, and recommendations. In addition, select chapters conclude with a section discussing the application of this topic in civilian practice, as potentially encountered by the rural or humanitarian relief surgeon. Additional new topics include: REBOA and endovascular techniques for hemorrhage control, updates in transfusion and resuscitation practice, active shooter situations, rural trauma management in developed nations, advancements in prehospital care and the Tactical Combat Casualty Care (TC3) course, and discussion of the newest generations of topical hemostatic agents and tourniquets. These additions serve to both enhance the breadth and depth of the material relevant to military surgeons, but should also further expand the applicability and interest in this work to all civilian trauma surgeons.
Keywords: Medicine.; Emergency medicine.; Surgery.; Abdominal surgery.; Thoracic surgery.; Traumatology.; elektronické knihy; electronic books